Functional outcome of intertrochanteric fractures in elderly patients with proximal femoral nail: retrospective study - Murugesan, Angatha Kumar; Govindasamy, Rajesh; Ismail, Patel Yahya (International Journal of Research in Orthopaedics, 2019)
Background: Intertrochanteric fractures are disabling injuries in elderly population and they are the most frequently operated fracture type which has the highest postoperative fatality rate of all surgically treated fractures. The objective of the study was to evaluate the functional outcomes of intertrochanteric fractures treated with proximal femoral nail (PFN) in elderly patients. Methods: A retrospective study of 24 patients, all above 60 years treated with PFN between March 2016 to April 2018. Data collected include age, sex, mechanism of injury, type of fracture pattern according to Boyd and Griffin’s classification. Patients were followed up at intervals of 6, 12, 18 and 24 weeks and final results were evaluated using Kyle’s criteria at the end of 24th week. All patients had a minimum follow up of one year. Results: The study included 24 patients, 10 males, 14 females with mean age of 75.77 years (range: 60-82 years). The fracture union rate was 96% and average union time was 14.2 weeks. Our results were excellent (80%), good (8%), fair (8%) and poor (4%). Our complications include thigh pain (20%) shortening (20%), varus displacement (8%), knee and hip stiffness (8%), z effect (4%) and non-union (4%). Conclusions: PFN is a reliable fixation in intertrochanteric fractures only after good intraoperative reduction leading to high rate of bone union and with reduced rate of implant failure or complications.